Genome-wide identification, expression, and regulatory network analysis of wheat microRNAs responsive to Bipolaris sorokiniana - Kashyap, Natasha; Gurjar, Malkhan Singh; Basak, Poulami; Sun, Xizhe; Ma, Lisong; Kumar, Aundy; Kumari, Jyoti; Aggarwal, Rashmi; Saharan, Mahender Singh; Periyannan, Sambasivam (Frontiers in Plant Science, 2025)
Spot blotch, caused by Bipolaris sorokiniana, is an important disease that leads to significant economic losses in wheat globally. Due to the complexity of B. sorokiniana infection, identification of wheat lines with strong resistance to spot blotch is challenging. Hence, the introduction of effective disease management strategies through the manipulation of genes involved in B. sorokiniana–wheat interaction remains essential. MicroRNAs (miRNAs) play a vital role in gene regulation and are increasingly used to predict molecular networks and genes associated with disease development or resistance. In this study, we employed small RNA sequencing to profile miRNAs in a resistant (IC566637) and a susceptible (Agra Local) wheat genotype following B. sorokiniana infection. A total of 726 miRNAs, predominantly 21 to 22 nucleotides in length, were identified. Among these, 140 are differentially expressed (DE) and associated with the modulation of 894 genes. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed these target genes as secondary metabolites, ATB-binding cassette (ABC) transporters, nucleotide-binding leucine-rich repeat (NB-LRR), mitogen-activated protein kinase (MAPK) genes, and hormones associated with plant–pathogen interaction and defense signal transduction. The regulatory network constructed from this data highlights key miRNA–target interactions likely contributing to disease resistance. Quantitative RT-PCR validation of nine selected miRNAs and their corresponding target genes further supports their potential role in modulating wheat defense responses. These findings provide a comprehensive resource for understanding miRNA-mediated regulation in the wheat–B. sorokiniana pathosystem and identified promising candidate genes for future resistance breeding and genome editing efforts.